2015
DOI: 10.1155/2015/743169
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Dendritic Cell Function in Inflammation

Abstract: Dendritic cells (DC) are professional antigen presenting cells and link the innate and adaptive immune system. During steady state immune surveillance in skin, DC act as sentinels against commensals and invading pathogens. Under pathological skin conditions, inflammatory cytokines, secreted by surrounding keratinocytes, dermal fibroblasts, and immune cells, influence the activation and maturation of different DC populations including Langerhans cells (LC) and dermal DC. In this review we address critical diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 193 publications
1
37
0
1
Order By: Relevance
“…The DCs observed in atopic lesions are mainly of myeloid origin and comprise 2 populations: Langerhans cells and inflammatory DCs. It was observed that Langerhans cells are involved in Th2 polarization, while inflammatory DCs promote Th1 polarization in chronic lesions [105,106]. T reg cells play an important role in AD.…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…The DCs observed in atopic lesions are mainly of myeloid origin and comprise 2 populations: Langerhans cells and inflammatory DCs. It was observed that Langerhans cells are involved in Th2 polarization, while inflammatory DCs promote Th1 polarization in chronic lesions [105,106]. T reg cells play an important role in AD.…”
Section: Role Of Vitamin D In Certain Inflammatory Skin Diseasesmentioning
confidence: 99%
“…Maturation and activation of DCs are key steps in triggering the priming of autoreactive peripheral T cells, which then drive the development of inflammatory responses [16][17][18][19]. The effect of SSCE on DCs maturation was evaluated in R848-induced BMDCs.…”
Section: Discussionmentioning
confidence: 99%
“…Lin − ZBTB46 + MHC-II + CD141 + conventional DCs (or their CD8a + CD4 − murine counterparts) typically cross-present extracellular antigens to CD8 + T cells, while Lin − ZBTB46 + MHC-II + CD1c + conventional DCs (or their CD8a − counterparts in mice) express a distinct TLR pattern (Said & Weindl, 2015) and are particularly effective at inducing Th2 responses (O’Keeffe, Mok, & Radford, 2015). In cancer, however, CD11b + conventional DCs have been found to suppress CD8 + T cell function in tumor-bearing mice, among other potential mechanisms, via L-Arginine metabolism (Norian, et al, 2009).…”
Section: The Nature Of Regulatory Dcs In the Tumor Microenvironmentmentioning
confidence: 99%